Amplitude limits and nonlinear damping of shear-Alfvén waves in high-beta low-collisionality plasmas - J Squire; A A Schekochihin; E Quataert (New Journal of Physics, 2017)
This work, which extends Squire et al ( Astrophys. J. Lett. 2016 https://doi.org/10.3847/2041-8205/830/2/L25 830 https://doi.org/10.3847/2041-8205/830/2/L25 ), explores the effect of self-generated pressure anisotropy on linearly polarized shear-Alfvén fluctuations in low-collisionality plasmas. Such anisotropies lead to stringent limits on the amplitude of magnetic perturbations in high- β plasmas, above which a fluctuation can destabilize itself through the parallel firehose instability. This causes the wave frequency to approach zero, ‘interrupting’ the wave and stopping its oscillation. These effects are explored in detail in the collisionless and weakly collisional ‘Braginskii’ regime, for both standing and traveling waves. The focus is on simplified models in one dimension, on scales much larger than the ion gyroradius. The effect has interesting implications for the physics of magnetized turbulence in the high- β conditions that are prevalent in many astrophysical plasmas.